Near-infrared light-induced photothermal and immunotherapy system for lung cancer bone metastasis treatment with simultaneous bone repair - Guoqing Zhong; Yali Miao; Jielong Zhou; Yijie He; Wenjie Yang; Chongquan Huang; Yunhui Zhang; Jin Xiao; Bingqing Bai; Jiaqi Zhou; Renshan Li; Tiantian Wei; et al. (Bioactive Materials)
Approximately half of lung cancer patients experience bone metastasis, leading to bone loss, fracture, and other skeletal-related events. Although immunotherapies have significantly advanced the therapeutic landscape for lung cancer, bone metastases have an immunologically ''cold'' microenvironment, representing a challenging obstacle when treating lung cancer. The combination of immunotherapy and photothermal therapy (PTT) for treating tumor-induced bone defects holds promise for enhancing the efficacy of local tumor ablation and inhibiting tumor recurrence and metastasis through activating systemic immune responses. Herein, we developed an injectable hydrogel-based photothermal immunotherapy system (BP@Gel-CD[SA] hydrogel) incorporating STING agonists (SA) and black phosphorus nanosheets (BPNSs) for high-efficiency tumor elimination, immune activation, and bone regeneration. The photothermal and photodynamic activities of BPNSs induce hyperthermia and ROS-mediated apoptosis of tumor cells. Meanwhile, SA loaded into the nano-boxes in BP@Gel-CD[SA] hydrogel by host-guest interaction significantly activates the cGas-STING pathway. It stimulates immunogenic cell death (ICD), synergistically promoting immune cell infiltration. Single-cell RNA sequence analysis confirms the modulation of the tumor microenvironment (TME) through the PTT-mediated ICD effect and the transactivation of the cGAS-STING pathway in immune cells of the TME. More importantly, the system can significantly inhibit the growth of distant tumors via systemic immune activation and elicit long-term immune memory in addition to tumor eradication. In the long term, this hydrogel system can promote the formation of new bone at sites of tumor-induced bone destruction, improving bone strength in the affected area. Collectively, this strategy provides an effective and safe option for treating lung cancer bone metastases.